Institutional priorities and student engagement: a multi-stakeholder analysis of physical education in Israel - Ali Alayan; Ahmad Salhab; Paz Carmel; Ronit Ahdut HaCohen (Frontiers in Sports and Active Living)
BackgroundPhysical Education (PE) is crucial to the development of children and adolescents, promoting physical health, mental well-being, and academic achievement. Despite global guidelines advocating for structured physical activity (PA) in schools, PE often remains underprioritized, especially in systems with competing academic demands. This study investigates the perceptions of students, PE teachers, and school administrators in Israel regarding PE value, participation, and institutional support.MethodsA cross-sectional survey was conducted with 150 participants from six East Jerusalem secondary schools, including students (70%), PE teachers (20%), and administrators or other staff (10%). A validated questionnaire assessed attitudes toward PE, including actual and preferred instructional hours, extracurricular engagement, and perceived barriers. Instrument reliability was confirmed via Cronbach's alpha coefficients (≥0.70), and data were analyzed using descriptive statistics and chi-square tests.ResultsAlthough 83% of students rated PE as equally important as other academic subjects, 70.7% reported receiving only one hour per week. Students with more PE exposure were significantly more likely to engage in extracurricular PA, value PA, and feel that they have more accessible and supportive opportunities for sports participation in their surroundings (p < 0.01). Cross-group comparisons revealed perceptual gaps in students who reported lower environmental support than teachers and administrators (p = 0.003). While PE teachers were seen as encouraging in class, their influence outside scheduled hours was less evident. Students noted institutional barriers, including frequent cancellations of PE classes and limited extracurricular support. Nonetheless, enjoyment of PE remained high, with most barriers viewed as having only a minor impact.ConclusionThese findings highlight the need for expanded PE hours, more substantial institutional commitment, and coordinated stakeholder action to foster an active school culture in Israel. However, limitations such as the modest sample size and the geographic concentration in East Jerusalem may affect the generalizability of the findings.